2003
DOI: 10.1200/jco.2003.10.100
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Psychological Impact of Carrying a BRCA1/2 Mutation and Prophylactic Surgery: A 5-Year Follow-Up Study

Abstract: Our findings support the emerging consensus that genetic predisposition testing for BRCA1/2 does not pose major mental health risks, but our findings also show that the impact of prophylactic surgery on aspects such as body image and sexuality should not be underestimated, and that some women are at risk for high distress, and as a result, need more attentive care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
223
6
13

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 260 publications
(256 citation statements)
references
References 45 publications
12
223
6
13
Order By: Relevance
“…91 Another study of BRCA1/BRCA2 carriers with breast cancer reported greater perceived stress 5 years after testing. 90 A slight increase in distress also was observed in a 7-year follow-up study of BRCA1/BRCA2 carriers compared with noncarriers. 93 To date, there are limited long-term studies available for Lynch syndrome.…”
Section: Long-term Psychiatric/psychological Impact Of Testingmentioning
confidence: 79%
See 2 more Smart Citations
“…91 Another study of BRCA1/BRCA2 carriers with breast cancer reported greater perceived stress 5 years after testing. 90 A slight increase in distress also was observed in a 7-year follow-up study of BRCA1/BRCA2 carriers compared with noncarriers. 93 To date, there are limited long-term studies available for Lynch syndrome.…”
Section: Long-term Psychiatric/psychological Impact Of Testingmentioning
confidence: 79%
“…Initial long-term studies for BRCA1/BRCA2 focused on individuals without cancer and reported no differences in psychosocial outcomes between carriers and noncarriers at 3 years 89 or 5 years after testing. 90 The 5-year study included carriers, most of whom (91%) had undergone prophylactic surgery, which may have confounded the results. 90 However, another study of women who were at risk for hereditary breast cancer but who had not undergone prophylactic risk-reducing surgeries reported distress levels that were lower or similar to their baseline levels 5 to 8 years later 51 ; and all long-term distress was predicted by corresponding baseline levels of intrusion, avoidance, anxiety, and depression.…”
Section: Long-term Psychiatric/psychological Impact Of Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the revealed additional risk of pancreatic cancer elicited worries, most counselees persisted in genetic testing. In addition, general distress levels were low for both test acceptors and decliners compared with those reported after the first counseling session of other, treatable, hereditary types of cancer [22][23][24][25][26] and lower even than distress levels of the general population [27] when measured with the same distress questionnaires. The melanoma screening program may have had a reassuring effect given the high proportion of eligible individuals at risk that take part in the PLC.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] In general, no major long-term adverse psychological consequences seem to result from the genetic testing process with the exception of a consistently present subgroup of individuals who report distress. 7,9,10 Although what causes psychological difficulties for this subgroup is still unclear, it has been proposed that psychological adaptation should be analyzed not only at the individual perspective level but also in the context of the family interrelationships. 11 Presently, family members carry responsibility for notifying relatives about the presence of cancer-predisposing mutation.…”
Section: Introductionmentioning
confidence: 99%